Kinetics of Thermal Death of Bacteria - Moats, William A. (1971)
Experimental observations on thermal injury and death of bacteria in the stationary phase can be explained by assuming that death results from inactivation of (X(L)) of N critical sites. It is assumed: (i) that inactivation of individual sites occurs at random and follows first-order kinetics, (ii) that the critical sites are identical and of equal heat resistance, and (iii) the bacterial population is homogeneous in heat resistance. A method is described for calculating k (the rate constant for inactivation of individual sites), N (sites per cell), and X(L) (the number which must be inactivated to cause death under the experimental conditions used) from experimental data. Theoretical curves calculated by using this model are identical with experimental curves, providing support for the assumptions used. Calculated values of N and X(L) were 130 and 21.7 for Pseudomonas viscosa and 175 and 2.7 for Salmonella anatum. There is considerable uncertainty in the absolute values of N, but they are probably > 100. It is predicted that X(L) will vary depending on the recovery medium used after heating. This theory is consistent with all experimental observations on thermal injury and death of bacteria.